Efficacy Analysis of Hypofractionated Radiotherapy for Oligometastatic Tumors: A Retrospective Study - Qian Sun MD; Hanqing Zhao MS; Xianwen Zhang MS; Suli Zhang MS; Zelai He MD; Gengming Wang MD; Hao Jiang MS; Aili Xuan MS; Xianming Li MD (Technology in Cancer Research & Treatment)
Introduction Metastasis remains a major cause of death among patients with malignant tumors. Radiotherapy is one of the main modalities of cancer treatment. The rapid development of radiotherapy technology has enabled the widespread application of hypofractionated radiotherapy (HFRT) in clinical practice. This study aimed to evaluate the effect of HFRT on the survival and safety of patients with oligometastatic tumors. Methods We conducted a retrospective study that involved 65 patients with well-controlled primary tumors and 1–5 metastatic foci treated at the study site between January 2020 and December 2022. Patients were aged >18 years and had a ≥ 6-month life expectancy. The patients received standard treatments plus HFRT for all metastatic foci. The dose fractionation regimen was adjusted according to the location and size of the patient’s metastatic foci. The planning gross tumor volume of HFRT was 82.93 cm 3 (range: 10.12-562.80 cm 3 ), and the radiation dose range was 20 Gy/5 F–60 Gy/15 F. Progression-free survival (PFS), overall survival (OS), local control rates, and incidence of adverse events of the patients were observed. Results Among the 65 patients, the median follow-up time, PFS, and OS were 26 months (95% CI: 0.80-37.50), 15 months (95% CI: 9.36-20.64), and 28 months (95% CI: 16.71-39.29), respectively. The 1- and 2-year PFS were 53.8% and 40.0%, respectively, while the 1- and 2-year OS rates were 73.8% and 56.9%, respectively. In total, 13.8%, 55.4%, 20.0%, and 13.8% of patients showed complete response, partial response, stable disease, and progressive disease, respectively. Four patients developed grade 3 or worse adverse events, and no treatment-related deaths occurred. Conclusions HFRT showed favorable clinical efficacy and safety in patients with oligometastatic tumors, generally achieving a good OS rate. Further randomized trials should be conducted.